Answer:
3x^2 or 3x squared
Step-by-step explanation:
4x^2-x^2=3x^2
4x squared-x squared equals x squared
when subtracting squared it's like subtracting normal numbers
Answers:
x = 6
y = 6*sqrt(2)
=======================
Explanation:
To find these values, you can use the general template of a 45-45-90 triangle or you can use trig ratios
tan(45) = 1
tan(angle) = opposite/adjacent
tan(45) = x/6
1 = x/6
6*1 = x
x = 6
-------
sin(45) = 1/sqrt(2)
sin(angle) = opposite/hypotenuse
sin(45) = 6/y
1/sqrt(2) = 6/y
1*y = sqrt(2)*6
y = 6*sqrt(2)
Answer: Janey has $115, and Teresa has $230.
Step-by-step explanation:
Set x be the money that Janey have, then Teresa have 2x.
x + 2x = 345
3x = 345
x= $115
2x= 2(115)= $230
Answer:
376,038
Step-by-step explanation:
16934+359104=376,038
I believe the answer to that question is -20